Strategy Analysis of English Zone Implementation in Modern Islamic Boarding Schools in Preparation for Global-Communication - Yuliani, Novi Dwi; Noor, Pajrian; Rujani, Muhammad Rifqy (Linguistics and ELT Journal, 2024)
Proficiency in English today is intended as a tool for effective communication on a global stage, necessitating an update to traditional strategies. This article aims to identify alternative strategies within the English Zone program at modern Islamic boarding schools to support students' preparation for global communication and used descriptive qualitative research methodology. Three main steps were employed to achieve this goal: (1) understanding the existing concepts and strategies of the English Zone implementation, (2) identifying challenges and obstacles during the program’s implementation, and (3) formulating alternative strategies to enhance students' readiness for global communication through Focus Group Discussion (FGD). The analysis methods applied include statistical and descriptive analysis. The findings of this study indicate that Foreign Language Debate Practice and Students’ Discussion, with agreed-upon adjustments, are the alternative strategies within the English Zone program at modern Islamic boarding schools to help students prepare for the global communication era.